2007
DOI: 10.1096/fj.07-8770com
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐high mobility group box 1 monoclonal antibody ameliorates brain infarction induced by transient ischemia in rats

Abstract: The high mobility group box-1 (HMGB1), originally identified as an architectural nuclear protein, exhibits an inflammatory cytokine-like activity in the extracellular space. Here we show that treatment with neutralizing anti-HMGB1 monoclonal antibody (mAb; 200 microg, twice) remarkably ameliorated brain infarction induced by 2-h occlusion of the middle cerebral artery in rats, even when the mAb was administered after the start of reperfusion. Consistent with the 90% reduction in infarct size, the accompanying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
303
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 338 publications
(322 citation statements)
references
References 51 publications
15
303
1
3
Order By: Relevance
“…HMGB1, as a mediator of postischemic brain damage, plays a critical role in the development of brain infarction through the amplification of plural inflammatory responses in the ischemic region and could be an outstandingly suitable target for treatment for this damage [23] . Intravenous injection of a neutralizing, anti-HMGB1 monoclonal antibody provides a novel therapeutic strategy for ischemic stroke [24] . In addition, serum HMGB1 levels were significantly elevated in patients with myocardial ischemia and cerebral ischemia, suggesting that systemic HMGB1 levels are elevated in human ischemic disease [25] .…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1, as a mediator of postischemic brain damage, plays a critical role in the development of brain infarction through the amplification of plural inflammatory responses in the ischemic region and could be an outstandingly suitable target for treatment for this damage [23] . Intravenous injection of a neutralizing, anti-HMGB1 monoclonal antibody provides a novel therapeutic strategy for ischemic stroke [24] . In addition, serum HMGB1 levels were significantly elevated in patients with myocardial ischemia and cerebral ischemia, suggesting that systemic HMGB1 levels are elevated in human ischemic disease [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Other DAMPs may also contribute to microglia-mediated neurodegeneration after stroke. For example, the prototypical DAMP, highmobility group box 1 (HMGB1) is elevated in the serum of stroke patients (81), may be secreted from neurons triggering microglial activation (49), and contributes significantly to neurodegeneration after ischemia (69,81). Thus, further studies are needed to better understand the precise mechanisms by which immune cells and inflammatory signaling contributes to neurodegeneration after acute neuronal injury, as well as the relative roles of Zn 2þ in these processes.…”
Section: Zinc-dependent Signaling In Neuronal Deathmentioning
confidence: 99%
“…More interestingly, HMGB1 has been shown to play a pivotal role in pulmonary fibrosis, partly through reduction of fibroblast proliferation and downregulation of interleukin (IL)-1b levels. 7 Furthermore, some researchers have found that HMGB1 promotes secretion of vascular endothelial growth factor (VEGF) 8 and that treatment with anti-HMGB1 antibodies suppresses the activity of matrix metalloproteinase (MMP)-9, 9 both of which are involved in airway remodeling.…”
Section: Introductionmentioning
confidence: 99%